Salinization of soils of adyr as a result of irrigation farming in the possibility of its elimination - Koriyev Mirzokhid Rustamjonovich (Universitas Muhammadiyah Sidoarjo, 2019)
The article discusses the salinization of adipose soils as a result of the development of irrigated agriculture on these lands, especially because of the cultivation of moisture-loving crops, and a set of measures for its prevention is proposed.